STRATEGI KELOMPOK SADAR WISATA DALAM PENGUATAN DESA WISATA - Ingga Purwanti (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Abstract: Strategy is a determination of the goals and long-term goals of an organization and the use of a series of actions and allocation of resources needed to achieve these goals. The purpose of this study wasto determine the strategy of tourism conscious groups in strengthening tourism villages (kungkuk tourist villages) in Punten Village, Kec. Bumiaji Kota Batu. he type of research used is qualitative. Data sources: primary data and secondary data. Technique for selecting snowball sampling informants. Data collection through interviews, collection and documentation. Data were analyzed through a process of data reduction, data presentation and conclusions. Measuring the validity of the data by measuring the trust and certainty of the object of research using triangulation techniques. The results of this study indicate that the Tourism Awareness Group Strategy in strengthening tourism villages in Kundur tourist village is by considering tourism conscious groups so that they can assist in submitting to the Tourism Office, namely providing facilities and infrastructure to make facilities and make agreements in tourism promotions.Keywords: Strategy, strengthening, and tourist villageAbstrak: Strategi merupakan suatu penetapan dari tujuan dan sasaran jangka panjang suatu organisasi serta penggunaan serangkaian tindakan dan alokasi sumber daya yang diperlukan untuk mencapai tujuan tersebut. Tujuan penelitian ini adalah untuk mengetahui strategi kelompok sadar wisata dalam penguatan desa wisata (kampung wisata kungkuk) di Desa Punten, Kec. BumiajiKota Batu. Jenis penelitian yangdigunakan yaitu kualitatif.Sumber data: data primer dan data sekunder. Teknik penentuan informan snowball sampling. Pengumpulan data melalui wawancara, observasi dan dokumentasi.Data dianalisismelalui proses reduksi data, penyajian data dan penarikan kesimpulan. Pengukuran validitas keabsahan data dengan mengukur kepercayaan dan kepastian atas objek penelitian menggunakan teknik triangulasi.Hasil penelitian ini menunjukan bahwaStrategi Kelompok Sadar Wisata dalam penguatan desa wisata Kampung wisata kungkuk yaitudengan adanya kelompok sadar wisata sehingga dapat membantu dalamsuatu pengajuan kepada Dinas Pariwisata yaitu berupa sarana dan prasarana yang berbentuk fasilitasfasilitas dan sebagai pelaku dalam promosi wisata.Kata Kunci: Strategi, Penguatan, dan Desa wisata